(untitled) (Research, Society and Development, 2022)
The study aims to explore the perception of medical students in the face of the COVID-19 pandemic in relation to changes in the teaching and learning process. The data were obtained through the application of an electronic questionnaire to academics from the first to the sixth year of the course through the Google Forms platform in 2020. These data were descriptively analyzed with graphical representations in the Excel 14.0 program. It was observed that 76.6% did not assist in the care of patients with COVID-19. 72.4% reported that they did not receive training to face the pandemic as provided for by the “Brazil counts on me” program. 57% (57) said they were moderately harmed by online classes, considering the vast majority of contents were well used. Regarding mental health issues, 73.5% noticed some change in behavior during the interruption of university activities; 44.1% of academics do not consider their sleep to be restful, presenting themselves as tired upon waking up. As for the use of psychotropic drugs, 18.2% needed to increase the dose of medications already used and 13.7% needed to start using them. It is concluded that the theoretical classes and discussions of clinical cases that took place online were essential for the total interruption of the academic year follow-up and the aggravation of existing psychological problems and the diagnosis of new cases among students alert to the need to largest psychological support network to be offered by the university to medical students.